Genetic Relationship among Some Isolates of Rhizoctonia Solani Isolated from Some Infected Tomato Plants (Solanum lycopersicum L) - Intissar Al-Salami (Journal of Global Pharma Technology, 2016)
This study was carried out in the laboratory of Plant Virology at the Department of plants protection/ College of Agriculture/ University of Karbala to isolate and diagnose some isolates of fungi isolated from infected tomato plants in Najaf and Karbala provinces, Iraq. These isolates were diagnosed by using the polymerase chain reaction (PCR) technique and identifying the nucleotide sequence generated from PCR-amplified products using the universal primer pair ITS1 and ITS4. The analysis of nucleotide sequences, obtained from amplifying PCR Products, using the Basic Local Alignment Search Tool (BLAST) showed that all identified isolates belong to the fungus R. solani. From comparing the nucleotide sequences of the identified R. solani isolates, it was revealed a clear genetic variation among them as well as with other isolates of the same fungus previously registered in the National Center for Biotechnology Information (NCBI). The results also showed that two isolates among the other R. solani isolates were not previously registered in NCBI; their nucleotide identified sequences were deposited under the accession numbers: MH520074 and MH520071.Keywords: Rizoctonia solani, Tomato, PCR, Nucleotide sequence, and ITS1-ITS4.